แนวคิดการจัดบริการสาธารณะแนวใหม่ : การมีส่วนร่วมของประชาชน ต่อการบริหารงานภาครัฐ - อัศวพิชยนต์, ชวนากร; หลักคำ, พิจิตรา; บุญทับ, วิทยา; พีรพลพลากร, มานะ; ปักสิน, วิทวัส; พ่วงรอด, ยุวดี (Journal of Roi Kaensarn Academi, 2024)
New Public Service (NPS) is a service that emphasizes greater public participation in all development processes, and adjusts the attitudes and values ​​of politicians and civil servants, aiming to create an atmosphere suitable for participation, and increasing channels, mechanisms, and measures to support public participation, creating citizenship with public awareness, working as a collaborative network, and working together towards maximum benefit for the development of the quality of life of all citizens to live well, eat well, and be happy equally